Sosialisasi Peningkatan Pemahaman Remaja Tentang Identitas Nasioanal Sebagai Upaya Pencegahan Seks Bebas Di Sekolah Menengah Pertama Negeri 04 Kota Padang - Elwidarifa Marwenny; Mesrizal Mesrizal; Nicko Alfidan; Indah Ainul Fadillah; Indah Septri Ayunda; Khairani Latifa; Rodhia Fadila Herma; Veoni Sinta Nosi (GLOBAL SCIENTS PUBLISHER, 2025)
During adolescence, in child development, physical and mental readiness is very dependent on the development of older people in the family. Promiscuity is difficult to control, therefore more attention needs to be given to teenagers, providing boundaries in living a social life. The archipelago's perspective is related to the Indonesian nation itself, and the social environment in which it lives, which is the Indonesian nation's outlook on life based on Pancasila and the 1945 Constitution. Free sex often conflicts with the morals, religious norms, customs and culture that characterize the nation. For this reason, Archipelago Insight emphasizes the formation of national character through consistent moral, religious and cultural education. Indonesian insight is related to free sex and promiscuity, due to the influence of the local environment, lack of attention and supervision from parents, and lack of supervision by teaching staff at schools. The impacts of sexuality include physical changes, the development of the infectious disease HIV/AIDS, psychological impacts, and physiological impacts. The benefits of sex education include conveying sufficient understanding about free sex material, forming attitudes and providing an understanding of sex in all its varied manifestations, providing an understanding of the importance of moral values, knowledge about sexual mistakes and deviations, to reduce prostitution, as well as excessive sexual exploration. . Education and coaching must be able to provide a more in-depth understanding, including from parents and families.